Panorama Francophone 2 - French Ab Initio For The IB Diploma Coursebook (2023) - Danièle Bourdais (Cambridge, United Kingdom CAMBRIDGE UNIVERSITY PRESS, 2015)
Designed to support IB Language B ab initio French students, it is the second of two student's books covering the two year course. International in approach and containing material designed to engage older teenage learners, it requires students to think and reflect at a level suitable for an IB Diploma student while placing a strong emphasis on developing intercultural understanding and on French as a world language. ToK and CAS are fully integrated into the learning and all language is taught and practised in context.
Keywords: IB DP Resource Group 2 French -- IB DP Resource Group 2 French